Ciência e ética: Fritz Haber e a guerra química - Martines, Ivan (2021)
Among the various innovations used in World War I, such as armor, planes and submarines, chemical gases, used by Germany, France and England, proved to be one of the most lethal and fearsome weapons ever seen, whose development drew on action from several scientists, among them Fritz Haber, a German of Jewish descent, winner of the 1918 Nobel Prize in Chemistry, who not only spearheaded the research and development of a gas-based weapon, but also spearheaded its application on the battlefield . If science had awakened the illusion that it would be the incarnation of the myth of Prometheus for humanity, the First World War showed a much less noble face, to say the least, in face of the horrors arising from the systematic military use of scientific advances, leading to reflection that perhaps it would be more appropriate to associate her with the figure of Dr. Victor Frankenstein. Did the scientist and, by extension, Science, ultimately represent a path to the salvation or destruction of humanity? But would it be simple and pertinent to classify science in such a Manichean way and to judge it morally as a result of its discoveries and applications, even when it comes to its military use? And do it with its main representatives, the scientists? These are questions raised by this work, which seeks an analysis of the moral aspects of the use of scientific knowledge, in the light of the History of Science, addressing difficulties in doing it without incurring in anachronism, naivety or superficiality